Pembentukan Karakter Peserta Didik melalui Program Aplikasi Keagamaan di SMPN 3 Peterongan - Ardaniyatus Azzahrah; Muhammad Fahmi; Ali Mas’ud (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to describe the formation of students’ religious character through the religious application program at SMPN 3 Peterongan Jombang. This research employs a qualitative case study approach, with data collected through observation, in-depth interviews, and documentation. Data analysis uses the Miles, Huberman, and Saldana model, which includes data condensation, data display, and conclusion drawing. The findings show that the religious application program is systematically structured through activities such as Qur’an reading, surah memorization, daily amaliyah, worship practice, and various religious habituation activities, including the 5S culture, istighotsah, yellow book studies, Islamic commemoration days (PHBI), and the Ramadan short pesantren. This program contributes significantly to the formation of students’ religious character, including improved worship discipline, enhanced understanding of worship procedures, daily moral behavior, and consistent spiritual habits. However, the implementation still faces challenges such as low student discipline, teachers’ tardiness, and the absence of firm sanctions. Nevertheless, the school’s location within a pesantren environment and the integration of the national curriculum with the pesantren curriculum provide strong opportunities to strengthen the program. With improved activity management and continuous guidance, the religious application program has strong potential to optimally and sustainably develop students’ religious character. Keywords: Religious character, Religious application program, SMPN 3 Peterongan